THE ROLE OF TRAINING EMPLOYEES IN INCREASING LABOR PRODUCTIVITY - Bobur Maxmudov (Web of Journals Publishing, 2025)
This article provides a comprehensive analysis of the role of employee training in increasing labor productivity. In today's rapidly changing labor market, organizations need to continuously improve their employees' skills to maintain and develop their competitiveness. Employee training serves to update their professional knowledge and skills, increase motivation for work, quickly master innovative technologies, and effectively organize production processes. The study covers the forms of employee training (internal training, external courses, online education, etc.) and their impact on productivity based on examples. It also discusses advanced foreign experiences and their adaptation to national practice. At the end of the article, the strategic importance of continuous employee training in increasing labor productivity and recommendations for its organization are presented.
Keywords: Employee training, labor productivity, advanced training, professional development, training, motivation, innovation, production, online education, competitiveness, personnel policy, strategic management.